Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to find the equation of a circle which passes through these points $(5,10), (-5,0),(9,-6)$ using the formula $(x-q)^2 + (y-p)^2 = r^2$.

I know i need to use that formula but have no idea how to start, I have tried to start but don't think my answer is right.

share|cite|improve this question
Can you share what you've tried, and explain what you're having trouble with? You have three data points, and three variables to solve for. – user61527 Jun 8 '14 at 17:48
So far i have the following but it just doesn't seem to sit right with me as being correct Sqareroot[(9-5-5)^2 + (-6-0-10)^2] and that would be the radius – help Jun 8 '14 at 18:14
up vote 4 down vote accepted

I know i need to use that formula but have no idea how to start

\begin{equation*} \left( x-q\right) ^{2}+\left( y-p\right) ^{2}=r^{2}\tag{0} \end{equation*}

A possible very elementary way is to use this formula thrice, one for each point. Since the circle passes through the point $(5,10)$, it satisfies $(0)$, i.e.

$$\left( 5-q\right) ^{2}+\left( 10-p\right) ^{2}=r^{2}\tag{1}$$

Similarly to the second point $(-5,0)$:

$$\left( -5-q\right) ^{2}+\left( 0-p\right) ^{2}=r^{2},\tag{2}$$

and to $(9,-6)$:

$$\left( 9-q\right) ^{2}+\left( -6-p\right) ^{2}=r^{2}.\tag{3}$$

We thus have the following system of three simultaneous equations and the three unknowns $p,q,r$:

$$\begin{cases} \left( 5-q\right) ^{2}+\left( 10-p\right) ^{2}=r^{2} \\ \left( -5-q\right) ^{2}+p^{2}=r^{2} \\ \left( 9-q\right) ^{2}+\left( 6+p\right) ^{2}=r^{2} \end{cases}\tag{4} $$

To solve it, we can start by subtracting the second equation from the first

$$\begin{cases} \left( 5-q\right) ^{2}+\left( 10-p\right) ^{2}-\left( 5+q\right) ^{2}-p^{2}=0 \\ \left( 5+q\right) ^{2}+p^{2}=r^{2} \\ \left( 9-q\right) ^{2}+\left( 6+p\right) ^{2}=r^{2} \end{cases} $$

Expanding now the left hand side of the first equation we get a linear equation

$$\begin{cases} 100-20q-20p=0 \\ \left( 5+q\right) ^{2}+p^{2}=r^{2} \\ \left( 9-q\right) ^{2}+\left( 6+p\right) ^{2}=r^{2} \end{cases} $$

Solving the first equation for $q$ and substituting in the other equations, we get

$$\begin{cases} q=5-p \\ \left( 10-p\right) ^{2}+p^{2}-\left( 4+p\right) ^{2}-\left( 6+p\right) ^{2}=0 \\ \left( 4+p\right) ^{2}+\left( 6+p\right) ^{2}=r^{2} \end{cases} $$

If we simplify the second equation, it becomes a linear equation in $p$ only

$$\begin{cases} q=5-p \\ 48-40p=0 \\ \left( 4+p\right) ^{2}+\left( 6+p\right) ^{2}=r^{2} \end{cases} $$

We have reduced our quadratic system $(4)$ to two linear equations plus the equation for $r^2$. From the second equation we find $p=6/5$, which we substitute in the first and in the third equations to find $q=19/5$ and $r^2=1972/25$, i.e

$$\begin{cases} q=5-\frac{6}{5}=\frac{19}{5} \\ p=\frac{6}{5} \\ r^{2}=\left( 4+\frac{6}{5}\right) ^{2}+\left( 6+\frac{6}{5}\right) ^{2}= \frac{1972}{25}. \end{cases}\tag{5} $$

So the equation of the circle is

\begin{equation*} \left( x-\frac{19}{5}\right) ^{2}+\left( y-\frac{6}{5}\right) ^{2}=\frac{1972}{25}. \end{equation*}

share|cite|improve this answer

Suppose the points are $A,B,C$. Then intersect the equations of perpendicular bisectors of $AB$ and $BC$. This is the center of the desired circle. (with your notation $(p,q)$)

Now calculate the distance between $(p,q)$ and $A$. Now $r$ is also found.


share|cite|improve this answer

$\begin{vmatrix} x^2+y^2&x&y&1\\ 5^2+10^2&5&10&1\\ (-5)^2+0^2&-5&0&1\\ 9^2+(-6)^2&9&-6&1\\ \end{vmatrix}= \begin{vmatrix} x^2+y^2&x&y&1\\ 125&5&10&1\\ 25&-5&0&1\\ 117&9&-6&1\\ \end{vmatrix} = 0$

share|cite|improve this answer
The simplest answer. – whatever Jun 8 '14 at 20:12
what does it say ? – Fardad Pouran Jun 8 '14 at 21:00

if the problem has a solution (the three points are on a circle) then you only need to calculate the equations of the two mediators and the intersection should be the center and the distance between one of the points and this center gives you r.

share|cite|improve this answer
Perhaps you could show how? At least show some guidelines. – user88595 Jun 8 '14 at 18:19

This method that I wrote creates a circle object which has a radius and a centre point. (written in Objective-C but can be port to many other languages)

- (Circle*)findCirclePassingThroughPoint1:(CGPoint)point1 point2:(CGPoint)point2 point3:(CGPoint)point3{

    double x1 = point1.x;  double x2 = point2.x;  double x3 = point3.x;
    double y1 = point1.y;  double y2 = point2.y;  double y3 = point3.y;

    double mr = (y2-y1) / (x2-x1);
    double mt = (y3-y2) / (x3-x2);

    if (mr == mt) {
        return nil;

    double x = (mr*mt*(y3-y1) + mr*(x2+x3) - mt*(x1+x2)) / (2*(mr-mt));
    double y = (y1+y2)/2 - (x - (x1+x2)/2) / mr;

    double radius = pow((pow((x2-x), 2) +  pow((y2-y), 2)), 0.5);
    CGPoint center = CGPointMake(x, y);

    Circle *circle = [[Circle alloc] initWithRadius:radius andCenter:center];
    return circle;

share|cite|improve this answer
Are you sure that your solution covers all degenerate cases ? – ogerard May 5 '15 at 14:54

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.